Ottoman Empire and European Theatre II : the time of Joseph Haydn : from Sultan Mahmud I to Mahmud II (r.1730-1839) - Hüttler, Michael; Weidinger, Hans Ernst (Ottomania (Don Juan Archiv Wien), 2014)
The Time of Joseph Haydn: From Sultan Mahmud I to Sultan Mahmud II (r.1730-1839), the second volume of Ottoman Empire and European Theatre, explores the relationship between Western playwrights, composers and visual artists of the eighteenth-century and Turkish-Ottoman culture, as well as the interest of Ottoman artists in European culture. Twenty-seven contributions by renowned experts shed light on the mutual influences that affected society and art for both Europeans and Ottomans. Successor to the first volume of the series, The Age of Mozart and Sultan Selim III (1756-1808), this book exam.